Reformulasi Kebijakan Perizinan Berusaha di Indonesia: Tinjauan Terhadap Pencabutan PP No. 5 Tahun 2021 dan Penerbitan PP No. 28 Tahun 2025 - Fatma Ulfatun Najicha; Bambang Manumayoso; Waluyo .; Elizabeth Ayu Puspita Adi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This article explores the rationale behind the revocation of Government Regulation (GR) No. 5 of 2021 on Risk-Based Business Licensing and its replacement by GR No. 28 of 2025. Using a normative juridical approach, the study assesses the effectiveness of the existing regulatory framework and the urgency for reformulating Indonesia’s business licensing system. The findings indicate that the implementation of GR 5/2021 encountered significant challenges, including systemic fragmentation, poor inter-agency coordination, and limited legal certainty. GR 28/2025 introduces key reforms such as the full integration of the Online Single Submission (OSS) system, the implementation of a strict Service Level Agreement (SLA), and the expansion of regulated business sectors. These reforms mark a strategic step toward a more transparent, responsive, and integrated business licensing regime in Indonesia.